2012
DOI: 10.1111/j.1365-3164.2012.01095.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of topical biocide and antimicrobial susceptibility of Staphylococcus pseudintermedius from dogs

Abstract: While isolates were susceptible to most of the tested compounds, universal susceptibility to all compounds with potential antimicrobial activity cannot be assumed, and specific testing is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 30 publications
0
27
2
Order By: Relevance
“…In fact, clinical examination on day 28 did not reveal any signs of bacterial infection in any dog that completed the study, regardless of the treatment group. The active ingredient (chlorhexidine) contained in the two topical products used in this study has been previously shown to be effective against a variety of micro‐organisms in in vitro studies . Topical agents with 2–4% chlorhexidine have been compared to other antibacterial agents, such as ethyl lactate or 2.5% benzoyl peroxide, and found to be of equivalent or superior effectiveness in the treatment of bacterial overgrowth and superficial pyoderma .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, clinical examination on day 28 did not reveal any signs of bacterial infection in any dog that completed the study, regardless of the treatment group. The active ingredient (chlorhexidine) contained in the two topical products used in this study has been previously shown to be effective against a variety of micro‐organisms in in vitro studies . Topical agents with 2–4% chlorhexidine have been compared to other antibacterial agents, such as ethyl lactate or 2.5% benzoyl peroxide, and found to be of equivalent or superior effectiveness in the treatment of bacterial overgrowth and superficial pyoderma .…”
Section: Discussionmentioning
confidence: 99%
“…However, MICs reported for MRS isolates from pets in North America, Europe and Asia have so far remained low, likely to be exceeded by drug concentrations achievable with topical application. Amongst the almost 200 MRSP isolates included in recent in vitro studies, low MICs were found for chlorhexidine (≤16 μg/mL), miconazole (≤2 μg/mL), fusidic acid (≤2 μg/mL), mupirocin (≤0.5 μg/mL) and polymyxin B (≤4 μg/mL); only one isolate in a collection of 49 showed a MIC of 16 μg/mL to fusidic acid . In the three studies that included MRSA isolates from pets, MICs were at least one dilution higher than for MRSP, with individual outliers of MICs exceeding 256 μg/mL fusidic acid (6 of 102 isolates) …”
Section: Therapeutic Considerations For Mrs Infectionsmentioning
confidence: 99%
“…In dog-derived staphylococci, MICs of fusidic acid, chlorhexidine and miconazole have been low, 68 but geographical differences can be expected. 9,10 Since previous MIC studies have evaluated mainly North American staphylococcal isolates, 7,8 we determined current susceptibility in vitro of dog-derived European MRSA and MRSP strains and their methicillin-susceptible counterparts to fusidic acid, chlorhexidine and miconazole, and investigated the potential for synergistic interaction between miconazole and chlorhexidine.…”
Section: Introductionmentioning
confidence: 99%